Responsiveness and minimal important difference of the urticaria control test - Ohanyan, Tatevik; Schoepke, Nicole; Bolukbasi, Bediha; Metz, Martin; Hawro, Tomasz; Zuberbier, Torsten; Peveling-Oberhag, Adriane; Staubach, Petra; Maurer, Marcus; Weller, Karsten (Journal of allergy and clinical immunology, 2017)
Short Summary This study demonstrates the responsiveness of the Urticaria Control Test (UCT). Changes of its score by 3 points or more reflect a clinically relevant change of disease control (minimal important difference).